SIMULATION STUDY IN REORGANIZING DISPATCHING LAYOUT TO MINIMIZE DISPATCHING TIME - Norazlan, Nor Asmaa Alyaa; Saptari, Adi; Mohamad, Effendi; Sukarma, Lukman; Salleh, Mohd Rizal; Yahaya, Saifudin Hafiz (Journal of Advanced Manufacturing Technology (JAMT), 2016)
Reorganizing a layout entails a major adjustment to current layout and thorough planning is essential before a new layout implementation. This study is to reorganize current layout at dispatching area of a manufacturing industry which produces apparel products. Current arrangement at the dispatching area has brought to a poor efficiency rate of 48.74% that consumed 30.77 minutes to complete one dispatching job with distance travel of 162.83 meters. Witness simulation study is used in this project methodology and Facility Planning Process approach is applied in the experimental design to generate alternative layout. Result of the alternative layout has reduced the current time to 32.79% and only consumes 20.68 minutes to complete one dispatching job with shorter distance travel of 109.44 meters.